Rancang Bangun Business Intelligence Dashboard untuk Hasil Panen Tanaman Pangan Menggunakan Tableau pada Dinas Pertanian TPH Provinsi Sumatera Selatan - Ramdani Ferdian; Afriyudi Afriyudi; Fatoni Fatoni (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
This study aims to design and build a Business Intelligence Dashboard for food crop yield data using Tableau at the Food Crops and Horticulture Department of South Sumatra Province. The management of harvest data that still uses spreadsheets makes the analysis, reporting, and decision-making processes less effective. The study used a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation studies. Data processing implemented Data Preparation stages including Data Ingestion, Data Cleaning, Data Transformation, Data Integration, and Data Extraction, while system development used the Prototype method. The results showed that the dashboard was successfully built with six main visualizations, namely KPI, Rice Production Trends, Corn Production Trends, Total Commodity Comparison, Regional Production Map, and Regional Production Performance. The dashboard is equipped with interactive filters based on period, location, and commodity to facilitate data analysis. The analysis results showed that rice production was the highest in South Sumatra Province in 2024 at 2,909,411.67 tons with Banyuasin Regency as the largest producer, while corn production reached 2,501,856.62 tons. The dashboard has been published through Tableau Public and is able to increase the efficiency of monitoring, information presentation, and support faster, more accurate, and data-driven decision-making.